Nonstorm time dropout of radiation belt electron fluxes on 24 September 2013. Issue 7 (15th July 2016) - Su, Zhenpeng; Gao, Zhonglei; Zhu, Hui; Li, Wen; Zheng, Huinan; Wang, Yuming; Wang, Shui; Spence, H. E.; Reeves, G. D.; Baker, D. N.; Blake, J. B.; Funsten, H. O.; et al.
Abstract: Radiation belt electron flux dropouts during the main phase of geomagnetic storms have received increasing attention in recent years. Here we focus on a rarely reported nonstorm time dropout event observed by Van Allen Probes on 24 September 2013. Within several hours, the radiation belt electron fluxes exhibited a significant (up to 2 orders of magnitude) depletion over a wide range of radial distances ( L > 4.5), energies (∼500 keV to several MeV) and equatorial pitch angles (0°≤ α e ≤180°). STEERB simulations show that the relativistic electron loss in the region L = 4.5–6.0 was primarily caused by the pitch angle scattering of observed plasmaspheric hiss and electromagnetic ion cyclotron waves. Our results emphasize the complexity of radiation belt dynamics and the importance of wave‐driven precipitation loss even during nonstorm times. Key Points: Nonstorm time dropout of radiation belt electron fluxes Quasi‐linear simulation of electron radiation belt evolution Importance of wave‐driven precipitation loss for radiation belt dynamics